Test method for friction characterization of rivets - Wituschek, Simon; Kuball, Clara-Maria; Merklein, Marion; Lechner, Michael (Defect and Diffusion Forum, 2020)
Due to continuously increasing requirements on lightweight sheet metal constructions, new processes and technologies are necessary to face current and future challenges. A trend in lightweight construction is the multi-material mix with sheets of different geometric and mechanical properties. To manufacture these so-called composite structures, new joining technologies and methods are required. One possibility is the further development of the self-pierce riveting joining process. For the simulation and evaluation of new and adapted processes of self-pierce riveting, numerical models are used to investigate process parameters and constraints. Besides precise material models for the numerical simulation of this joining process, the identification of friction parameters between the individual sheets and rivet elements is necessary to achieve exact results. Thus, a method is necessary to identify the friction coefficients between rivet elements and sheets. Such a method is presented and evaluated in this work. Different process parameters like the relative speed are varied for the experimental investigations and an analysis of the respective influence on the resulting friction coefficients is conducted. For the use of the test set-up, coefficients of friction are determined for rivet elements “RIVSET® C 5.3x5.5” (Böllhoff GmbH) coated with Almac® in combination with two different sheet materials HCT590X+Z and EN-AW 6014.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Friction; Joining; Self-piercing riveting